Forage Sorghum (Sorghum bicolor): Overview and Management - Yoana Newman; John Erickson; Wilfred Vermerris; David Wright (EDIS)
SSAGR333, a 13-page illustrated fact sheet by Yoana Newman, John Erickson, Wilfred Vermerris, and David Wright, provides an overview of the types of sorgum, criteria for selection, cultural practices, pest management, and marketing strategies. Includes references. Published by the UF Department of Agronomy, July 2010.